The effect of Eurycoma Longifolia Jack (Tongkat Ali) on carbon tetrachloride-induced liver damage in rats - Alfaqeh, Hamoud Hussein Mohammed; Muhammad, Bala Yauri; Abdel Wahab, Emad Mohamad Nafie; Khorshid, Anuar (Penerbit USM, 2010)
We attempted to investigate possible hepatoprotective effect of Eurycoma longifolia jack (ELJ) using carbon tetrachloride (CC14)-induced acute hepatotoxicity model in rats. Hepatotoxicity was induced by oral administration of 4.0 mg/kg of CCI4 in corn oil (1:1) once to one experimental group of 5 rats. In three other similar groups, challenged doses (300, 750 and 1500 mg/kg respectively) of ELJ were given one day before and one hour after 4.0 mg/kg CC14 and then once daily for three consecutive days. Three other groups of 5 rats each serving as controls were administered with distilled water, corn oil and ELJ (750 mg/kg) only respectively. Rats were sacrificed on day three (corn oil and CC14 treated groups) and on day 4 (distilled water, ELJ alone and CC14 with graded doses of ELJ treated groups). Samples of blood and liver tissue were taken for biochemical (serum) and histopathological examinations to assess hepatoprotection of ELJ against CC14-induced hepatotoxicity. In the low (300 mg/kg) and medium (750 mg/kg) doses ELJ-treated groups, CCI4 was found to induce moderate inflammation, fatty acid change and necrosis of hepatocytes while in the high (1500 mg/kg) dose ELJ, CC14 induced severe inflammation, fatty acid change and necrosis of hepatocytes. Biochemical measurements of alanine aminotransferase (ALT) and alkaline phosphatase (ALP) shows a moderate and insignificant reduction of serum levels in the low dose ELJ group but a more significant reduction in the medium and high dose ELJ groups when compared with the CC14-only group. The increase in serum total bilirubin caused by CC14 was non-significantly reduced by all the doses of ELJ. Animals treated with CC14 alone and in groups treated with both CC14 and graded doses of ELJ had a reduction in body weight, food and water intake. In ELJ (750 mg/kg)-only treated group, no such reduction in body weight, food and water intake was observed. This observation suggest that ELJ administered alone did not cause any toxic effect to the liver but in combination with CCI4, appeared to synergise the CC14-induced hepatotoxicity which increases as the dose of ELJ is increased. The anorexic, hypodypsic and reduced body weight evident in the CC14-only and in ELJ plus CC14-treated groups but not in animals treated with ELJ-alone, suggests that ELJ alone does not induce anorexia, hypodypsia or loss of weight. In conclusion, the results of our study suggest that ELJ is not hepatotoxic when given alone and appeared to have some degree of protective effects in rats against CC14-induced hepatotoxicity.